A1 not A2A adenosine receptors play a role in cortical epileptic afterdischarges in immature rats - Mareš, Pavel (Journal of neural transmission (Vienna, Austria, 2014)
Endo- as well as exogenous adenosine exhibits anticonvulsant action. Participation of individual types of adenosine receptors was studied in present experiments in immature rats. Cortical epileptic afterdischarges were used as a model in rat pups 12, 18 and 25 days old. CCPA, an agonist of A1 adenosine receptors, decreased markedly duration of afterdischarges whereas DPCPX, an antagonist of A1 receptors, exhibited strong proconvulsant action. Action of either drug was best expressed in 12-day-old rats and it decreased with age. Drugs influencing A2A adenosine receptors (agonist CGS21680 and antagonist ZM241385) did not exhibit systematic effects in our model. Motor phenomena accompanying cortical stimulation or epileptic afterdischarge were never influenced by any of the four drugs studied. A1 adenosine receptors are important in the model of cortical seizures, especially in the youngest group studied.
Keywords: Receptors, Adenosine A2; Electric Stimulation; biofyzika; Dose-Response Relationship, Drug; akční potenciály; analýza rozptylu; novorozená zvířata; purinergní látky; věkové faktory; Analysis of Variance; krysa rodu Rattus; zvířata; Action Potentials; mozková kůra; potkani Wistar; Cerebral Cortex; Animals, Newborn; Rats, Wistar; Male; receptory adenosinové A2; Purinergic Agents; Rats; vztah mezi dávkou a účinkem léčiva; Age Factors; elektrická stimulace; receptor adenosinový A1; Animals; mužské pohlaví; Biophysics; Receptor, Adenosine A1